1984
DOI: 10.1007/bf00412556
|View full text |Cite
|
Sign up to set email alerts
|

PUVA-induced erythema and changes in mechanoelectrical properties of skin. Inhibition by tocopherols

Abstract: Influence of antioxidants on two phototoxic effects of 8-methoxypsoralen (8-MOP) was studied: erythema and changes in mechanoelectrical properties of skin. alpha-Tocopherol and its analogs with shortened lateral hydrocarbon chains at C2-atoms of chromane groups (chromanols) were used as antioxidants. alpha-Tocopherol and its analogs inhibited both phototoxic effects of 8-MOP. Inhibition was observed only if antioxidants were present in skin during irradiation. When applied after irradiation these antioxidants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…This corresponds with the observation that AT-ac, without a free aromatic hydroxyl, did not protect against PUVA-induced erythema (Potapenko et al 1984). When in our experiments, rats were pre-treated with AT-ac on 4 consecutive days before 8-MOP was applied (experiment 2), a protective effect similar to that of AT with regard to protein and DNA/RNA binding was observed.…”
Section: D: By Quenching Reactive Intermediatessupporting
confidence: 88%
See 2 more Smart Citations
“…This corresponds with the observation that AT-ac, without a free aromatic hydroxyl, did not protect against PUVA-induced erythema (Potapenko et al 1984). When in our experiments, rats were pre-treated with AT-ac on 4 consecutive days before 8-MOP was applied (experiment 2), a protective effect similar to that of AT with regard to protein and DNA/RNA binding was observed.…”
Section: D: By Quenching Reactive Intermediatessupporting
confidence: 88%
“…Thiols offered strong protection against in vivo photobinding of 8-MOP as well as CPZ (Van den Broeke, to be published). Potapenko et al (1984) demonstrated that protection against PUVA-induced erythema offered by tocopherol increased with the concentration of the antioxidant. However, at higher concentrations they observed that the protective effect diminished.…”
Section: D: By Quenching Reactive Intermediatesmentioning
confidence: 97%
See 1 more Smart Citation
“…In mice, topical vitamin E decreased UV-induced effects such as lipid peroxidation (Lopez-Torres et al, 1998), cutaneous photoaging (Bissett et al, 1990;Jurkiewicz et al, 1995), immunosuppression (Gensler and Magdaleno, 1991;Yuen and Halliday, 1997;Steenvoorden and Beijersbergen v Henegouven, 1999), and photocarcinogenesis (Bissett et al, 1990;Gensler and Magdaleno, 1991;Yuen and Halliday, 1997;Burke et al, 2000). Topical application of vitamin E to human skin has also been found to reduce UVB-and PUVA-induced skin erythema (Potapenko et al, 1980(Potapenko et al, , 1984.…”
Section: Discussionmentioning
confidence: 92%
“…Application of a-tocopherol before psoralen plus UVA therapy protected subjects against erythema in a dose-dependent fashion. 91 In addition, human skin pretreated with 5% vitamin E before UV exposure inhibited the normal up-regulation of human macrophage metalloelastase by 47%. 92 Human macrophage metalloelastase is involved in the degradation of elastin and is found primarily in chronically sunexposed areas of the skin, colocalizing with areas of solar elastosis.…”
Section: Vitamins As Therapymentioning
confidence: 99%